Analisis Kandungan Formalin, Boraks, dan Protein dalam Mie Basah - Elisabet Nani; Yari Mukti Wibowo (Biomedika, 2019)
Wet noodles are flour-based foods and are widely consumed by the community because the processing is relatively easy. So that wet noodles are more durable and more chewy, sometimes wet noodles are added with formalin and borax. Therefore this study will analyze the formalin and borax content in wet noodles. According to SNI 2987: 2015 there should be no formalin and borax preservatives in wet noodles, and the minimum level of protein is 9.5%. Determination of qualitative analysis of formaldehyde using color testing while qualitative analysis of borax uses a flame test. Determination of protein content in wet noodle samples using the Kjeldahl method. Based on the results of research on 3 samples of wet noodles sold at Pasar Gedhe, Surakarta City and its surroundings, negative or no formaldehyde and borax results were obtained, so they meet the quality requirements of wet noodles based on SNI 2987 : 2015. The average protein content in wet noodles is very small in sample A of 0.31%, sample B is 1, 22% and sample C is 2.61%, so they do not meet the quality requirements of wet noodles based on SNI 2987 : 2015.